Co-coated CoS composite material, preparation method thereof and application of Co-coated CoS composite material in preparation of nano gas sensitive sensor

By using the gas-sensitive sensor prepared by Co@CoS composite material, the problem of detecting the decomposition components of SF6/N2 insulating gas in GIS is solved, and high sensitivity detection for specific gases and excellent temperature adaptability are achieved.

CN119706963APending Publication Date: 2025-03-28GUIZHOU POWER GRID CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411594422.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-09
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively detect the characteristic decomposition components generated by the decomposition of SF6/N2 insulating gas in gas insulating combination appliances (GIS), resulting in equipment failure and power system stability being threatened.

Method used

The platinum interdigital electrode was prepared using Co@CoS composite material to construct a gas-sensitive sensor for detecting the SF6/N2 decomposed component gas. This material is made by calcining a cobalt-based zeolite imidazole ester framework structure material and sulfur powder, and has high responsiveness and excellent detection temperature.

Benefits of technology

At 200°C, the Co@CoS composite nanogas sensitive sensor showed strong response to gases such as SO2F2, SO2 and H2S, and the material was not damaged significantly. It has high sensitivity and good recovery characteristics, and is suitable for the detection of SF6/N2 decomposition components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119706963A_ABST
    Figure CN119706963A_ABST
Patent Text Reader

Abstract

The invention discloses a Co-coated CoS composite material, a preparation method thereof and application of the Co-coated CoS composite material in preparation of a nano gas sensitive sensor, and belongs to the field of novel nano materials and the technical field of gas sensitive sensing. In the Co-coated CoS composite material, the Co-based catalyst can promote chemical reaction by using the adsorbability of cobalt, and the polar bond of CoS enhances the adsorbability of the material and prolongs the service life of the catalyst. According to the invention, a cobalt-based zeolite imidazate framework structure material (Co-ZIF) is used as a precursor, a high-response Co-coated CoS nano gas-sensitive material suitable for detecting SF6 / N2 decomposition components is prepared through vulcanization, and a novel resistance-type gas-sensitive sensor based on the Co-coated CoS composite material is provided. According to the present invention, the prepared material has characteristics of simple preparation process, good responsiveness to 200ppm SO2F2, SO2 and H2S at 200 DEG C, no significant damage, and excellent adsorption capacity and suitable detection temperature when the material is used for SF6 / N2 decomposition component detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of novel nanomaterials and gas-sensitive sensor technology, and specifically relates to a Co@CoS composite material and a preparation method thereof and application in the preparation of a nano gas-sensitive sensor. Background Art

[0002] Gas insulated switchgear (GIS) is an advanced high-voltage device that uses SF6 / N2 gas as the insulating medium and encapsulates key equipment such as circuit breakers, disconnectors, busbars and lightning arresters in a closed cavity. It is widely used in ultra-high voltage and extra-high voltage power grid systems. Its main function is to receive and distribute electrical energy in the distribution link, while controlling and protecting circuits and other power equipment.

[0003] In the power grid system, when insulation defects occur inside the equipment, causing local discharge and local overheating, the insulating medium will decompose, a series of chemical reactions will occur, and some stable gas decomposition components will be generated. Among them, the decomposition of the insulating oil and paper of the transformer mainly produces H2, CH4, C2H6, C2H4, C2H2, C3H8, C3H6, CO, CO2, etc.; the SF6 / N2 and solid insulation damage of the GIS mainly produce SO2, SOF2, SO2F2, H2S, H2S, CS2, HF, CO, CO2, etc.; the decomposition of XLPE of the high-voltage cable will produce trace amounts of CO, CO2, C2H4, C2H6, etc. If the fault characteristic gas is not detected in time, the equipment defects are discovered early, and the corresponding operation and maintenance measures are taken in time, the defects will further deteriorate, and eventually lead to equipment failure and insulation breakdown, causing great harm to the stable operation of the power system.

[0004] In order to solve the important issue of how to evaluate the system operating status under insulation faults, monitoring the characteristic decomposition components generated by the decomposition of SF6 / N2 insulating gas can serve as an important reference and is of great significance for ensuring the safety and stability of power transmission and transformation equipment. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] One of the contents of the present invention is to prepare platinum interdigital electrodes with Co@CoS composite materials and construct a gas sensor to detect the decomposition component gases of SF6 / N2; the second content of the present invention is to supplement the deficiencies of existing resistive gas sensors in detecting the decomposition components of SF6 / N2, and propose a new resistive gas sensor based on Co@CoS composite materials, which can have a strong response to most of the decomposition component gases of SF6 / N2 at 200°C, has high sensitivity, and improves some defects of the existing resistive gas sensors in detecting.

[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a Co@CoS composite material.

[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:

[0010] Dissolve Co(NO3)2·6H2O in methanol to obtain solution A; dissolve dimethylimidazole in methanol to obtain solution B;

[0011] The solution A and the solution B are mixed and stirred continuously, and the obtained stirred product is allowed to stand for self-reaction; the self-reaction product is washed and dried to obtain a cobalt-based zeolite imidazolate framework structure material Co-ZIF;

[0012] Co-ZIF and sulfur powder were calcined in a closed argon atmosphere and after cooling to room temperature, a Co@CoS composite material was obtained.

[0013] As a preferred embodiment of the method for preparing the Co@CoS composite material of the present invention, in the solution A, the mass volume ratio of Co(NO3)2·6H2O to methanol is 1.2-2 g: 50-100 ml.

[0014] As a preferred embodiment of the preparation method of the Co@CoS composite material of the present invention, wherein: in the solution B, the molar concentration of dimethylimidazole is 300-500×10 -3 The mass volume ratio of mol / L dimethylimidazole and methanol is 3-4.2g:50-100ml.

[0015] As a preferred embodiment of the method for preparing the Co@CoS composite material of the present invention, the stirring speed is 300-400 r / min and the stirring time is 0.5-1 min.

[0016] As a preferred embodiment of the method for preparing the Co@CoS composite material of the present invention, the self-reaction time is 12 to 15 hours.

[0017] As a preferred solution of the method for preparing the Co@CoS composite material of the present invention, the mass ratio of the Co-ZIF to the sulfur powder is 1:2-4.

[0018] As a preferred embodiment of the preparation method of the Co@CoS composite material of the present invention, the calcination comprises the following steps: the calcination temperature is 650-800°C, the calcination time is 1-3h, and the heating rate is 30-50°C / min.

[0019] Another object of the present invention is to overcome the deficiencies in the prior art and provide a Co@CoS composite material.

[0020] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of a Co@CoS composite material in the preparation of a nano gas sensor.

[0021] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:

[0022] The Co@CoS composite material is dissolved in ethylene glycol, dispersed evenly, and then coated on the built-in platinum interdigital electrodes of the sensor using a silk screen plate; vacuum drying is performed to form a stable film of the Co@CoS composite material covering the interdigital electrode sensing area, thereby obtaining a Co@CoS composite material nano gas sensor;

[0023] Wherein, the vacuum drying time is 8 to 12 hours.

[0024] As a preferred solution of the nano gas sensor based on Co@CoS composite material described in the present invention, the nano gas sensor is used for detecting the decomposition components of SF6 / N2 in gas-insulated switchgear.

[0025] Beneficial effects of the present invention:

[0026] Compared with the existing detection technology, the Co@CoS composite material nano gas sensor of the present invention has the following advantages: at 200°C, the gas-sensitive response to 200ppm of SO2F2, SO2 and H2S can reach a very good value, and there is no obvious damage to the material. The prepared Co@CoS composite material is used as a SF6 / N2 decomposition component detection material, which not only shows excellent gas-sensitive adsorption ability, but also has excellent detection temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0028] Figure 1 is the XRD pattern of Co@CoS composite;

[0029] Figure 2 is the SEM image of Co@CoS composite material. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0033] The raw materials used in the present invention are all commercially available unless otherwise specified.

[0034] The performance of the material prepared in the embodiment of the present invention was tested as follows:

[0035] ① Detection parameter setting: The working temperature of Co@CoS composite material is set to 150-300℃, and the gas concentration is 50-350ppm; ② Gas-sensitive test method: The prepared sensor is installed in the test device, and helium is introduced until the initial resistance value of Co@CoS composite material is stable, recorded as R0, and then the gas to be tested is introduced to obtain a stable reaction resistance, recorded as R1, and the gas to be tested is removed and helium ventilation is restored until the resistance value of Co@CoS composite material is restored to be stable, recorded as R2, and the response ability of Co@CoS composite material to the three gases is analyzed by S1=R0 / R1, and the recovery ability of Co@CoS composite material is analyzed by S2=R0 / R2.

[0036] Gas-sensitive detection of SO2F2, H2S and SO2 was carried out under the conditions of test temperature of 200°C and gas concentration of 200ppm. The time for introducing the detection gas was 50s, the time for selecting the detection point, i.e., the stabilization time, was 250s, and the time for cutting off the detection gas and restoring the helium supply was 350s.

[0037] Example 1

[0038] This embodiment provides a method for preparing a nano gas sensor based on a Co@CoS composite material, specifically:

[0039] 1) Add 1.455 g of Co(NO3)2·6H2O to 50 ml of methanol, seal the cup with plastic wrap, place it on a magnetic stirrer and stir until the powder is dissolved to obtain solution A;

[0040] 2) Take 3.284 g of dimethylimidazole (400 × 10 -3 M) was added to 50 ml of methanol, and after sealing with plastic wrap, the measuring cup was placed on a magnetic stirrer and stirred until the powder was dissolved to obtain solution B;

[0041] 3) The products obtained from solution A and solution B were mixed and placed in a centrifuge at a speed of 300 r / min for continuous stirring for 0.5 min, and then the stirred product was allowed to stand for 13 h for self-reaction. After the reaction was completed, it was washed with ethanol for 3 times and dried at 60° C. to obtain a well-structured cobalt-based zeolite imidazolate framework material Co-ZIF;

[0042] 4) Take 100 mg of the precursor Co-ZIF and 300 mg of sulfur powder, put them separately in the same porcelain boat, cover the porcelain boat lid, and calcine them at 650°C for 2 h in a closed argon atmosphere with a heating rate of 50°C / min. After cooling to room temperature, the Co@CoS composite material with good morphology can be obtained.

[0043] 5) The built-in platinum interdigital electrodes of the sensor are ultrasonically rinsed with deionized water; the Co@CoS composite material is dissolved in ethylene glycol, dispersed evenly, and then coated on the electrode using a silk screen; the sensor is placed in a vacuum oven and baked under vacuum conditions until the ethylene glycol is completely evaporated and the Co@CoS composite material forms a stable film covering the interdigital electrode sensing area, thereby obtaining a Co@CoS composite material nano gas sensor.

[0044] Figure 1 This is the XRD diagram of the Co@CoS composite material. It can be seen that the characteristic peaks of Co single substance and CoS are both reflected in the test results, and the peak intensity is relatively high, indicating that the material is a composite phase of Co and CoS.

[0045] Figure 2This is the SEM image of the Co@CoS composite material. It can be clearly seen that the Co@CoS composite material has a blocky structure and has a large number of particles attached to the surface, indicating that its surface area is large and also reflects that the material has strong adsorption.

[0046] Example 2

[0047] This embodiment provides a method for preparing a nano gas sensor based on a Co@CoS composite material, specifically:

[0048] 1) Take 2.037g Co(NO3)2·6H2O and add it to 70ml methanol. After sealing with plastic wrap, place the measuring cup on a magnetic stirrer and stir until the powder is dissolved to obtain solution A.

[0049] 2) Take 4.598 g of dimethylimidazole (400 × 10 -3 M) was added to 70 ml of methanol, and after sealing with plastic wrap, the measuring cup was placed on a magnetic stirrer and stirred until the powder was dissolved to obtain solution B;

[0050] 3) The products obtained from solution A and solution B were mixed and placed in a centrifuge at a speed of 400 r / min for continuous stirring for 1 hour, and then the stirred product was allowed to stand for 10 hours for self-reaction. After the reaction was completed, it was washed with ethanol for 3 times and dried at 80° C. to obtain a well-structured cobalt-based zeolite imidazolate framework material Co-ZIF;

[0051] 4) Take 150 mg of the precursor Co-ZIF and 450 mg of sulfur powder, put them separately in the same porcelain boat, cover the porcelain boat lid, and calcine them at 800 °C for 3 h in a closed argon atmosphere with a heating rate of 25 °C / min. After cooling to room temperature, the Co@CoS composite material with good morphology can be obtained.

[0052] 5) The built-in platinum interdigital electrodes of the sensor are ultrasonically rinsed with deionized water; the Co@CoS composite material is dissolved in ethylene glycol, dispersed evenly, and then coated on the electrode using a silk screen; the sensor is placed in a vacuum oven and baked under vacuum conditions until the ethylene glycol is completely evaporated and the Co@CoS composite material forms a stable film covering the interdigital electrode sensing area, thereby obtaining a Co@CoS composite material nano gas sensor.

[0053] Example 3

[0054] This embodiment provides a method for preparing a nano gas sensor based on a Co@CoS composite material, specifically:

[0055] 1) Take 2.91 g of Co(NO3)2·6H2O and add it to 100 ml of methanol. After sealing with plastic wrap, place the measuring cup on a magnetic stirrer and stir until the powder is dissolved to obtain solution A.

[0056] 2) Take 6.568g dimethylimidazole (400×10 -3 M) was added to 70 ml of methanol, and after sealing with plastic wrap, the measuring cup was placed on a magnetic stirrer and stirred until the powder was dissolved to obtain solution B;

[0057] 3) The products obtained from solution A and solution B were mixed and placed in a centrifuge at a speed of 600 r / min for continuous stirring for 1.5 h, and then the stirred product was allowed to stand for 12 h for self-reaction. After the reaction was completed, it was washed with ethanol for 3 times and dried at 100° C. to obtain a well-structured cobalt-based zeolite imidazolate framework material Co-ZIF;

[0058] 4) Take 200 mg of the precursor Co-ZIF and 600 mg of sulfur powder, put them separately in the same porcelain boat, cover the porcelain boat lid, and calcine them at 900 °C for 4 h in a closed argon atmosphere with a heating rate of 20 °C / min. After cooling to room temperature, the Co@CoS composite material with good morphology can be obtained.

[0059] 5) The built-in platinum interdigital electrodes of the sensor are ultrasonically rinsed with deionized water; the Co@CoS composite material is dissolved in ethylene glycol, dispersed evenly, and then coated on the electrode using a silk screen; the sensor is placed in a vacuum oven and baked under vacuum conditions until the ethylene glycol is completely evaporated and the Co@CoS composite material forms a stable film covering the interdigital electrode sensing area, thereby obtaining a Co@CoS composite material nano gas sensor.

[0060] The materials prepared in the above examples were subjected to gas-sensitive detection of SO2F2, H2S and SO2 under the conditions of test temperature of 200°C and gas concentration of 200 ppm. The results are shown in Table 1.

[0061] Table 1

[0062]

[0063]

[0064] It can be seen from the table that the Co@CoS composite gas-sensitive material has a strong response to SO2F2, the response ratio S1 can reach 2.29, and the recovery ratio S2 can reach 1.05, indicating that the gas-sensitive material has a good recovery characteristic after detecting SO2F2, that is, it can almost recover to the initial state after the test.

[0065] The Co@CoS composite gas-sensitive material also has a good response to H2S, with a response ratio S1 of 1.33 and a recovery ratio S2 of 1.11, indicating that the material is less damaged and has strong structural retention properties.

[0066] The Co@CoS composite gas-sensitive material also has a strong response to SO2, and the response ratio S1 can also reach 2.29, 2.45 and 2.69, and the recovery ratio S2 can also reach 1.04, 1.12 and 1.11, indicating that the gas-sensitive material also has excellent recovery characteristics after detecting SO2.

[0067] Comparative Example 1

[0068] The difference between this comparative example and Example 1 is that the mixed solution is not allowed to stand for self-reaction, but is heated to increase the degree of reaction, the temperature is 80° C., and the time is 12 hours.

[0069] Comparative Example 2

[0070] The difference between this comparative example and Example 1 is that high-temperature calcination in a H2 / Ar gas atmosphere is not performed, and the reaction kettle is directly subjected to a hydrothermal reaction to obtain a product, which is then dried and continued according to step (5).

[0071] The material obtained in the above comparative example was subjected to gas-sensitive detection for SO2F2, H2S, and SO2. The detection conditions were a test temperature of 200°C and a gas concentration of 200 ppm. The results are shown in Table 2.

[0072] Table 2

[0073]

[0074]

[0075] The present invention uses cobalt-based zeolite imidazolate framework structure material (Co-ZIF) as a precursor, and obtains a highly responsive Co@CoS nano gas-sensitive material suitable for detecting SF6 / N2 decomposition components by sulfurization, and proposes a new type of resistive gas sensor based on Co@CoS composite material. In the Co@CoS composite material, the Co-based catalyst can promote chemical reactions by utilizing the adsorption of cobalt, and the polar bonds of CoS enhance the adsorption of the material and the life of the catalyst.

[0076] The Co@CoS composite nano gas sensor of the present invention exhibits good responsiveness to 200ppm SO2F2, SO2 and H2S at 200°C, and the material has no significant damage, and exhibits excellent adsorption capacity and suitable detection temperature for SF6 / N2 decomposition component detection. The Co@CoS composite nano gas sensor of the present invention has a strong response to most SF6 / N2 decomposition component gases and has good sensitivity, and is a nano gas-sensitive material with great practical application value.

[0077] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a Co@CoS composite material, characterized in that: include, Dissolve Co(NO3)2·6H2O in methanol to obtain solution A; dissolve dimethylimidazole in methanol to obtain solution B; The solution A and the solution B are mixed and stirred continuously, and the obtained stirred product is allowed to stand for self-reaction; the self-reaction product is washed and dried to obtain a cobalt-based zeolite imidazolate framework structure material Co-ZIF; Co-ZIF and sulfur powder were calcined in a closed argon atmosphere and after cooling to room temperature, a Co@CoS composite material was obtained.

2. The method for preparing the Co@CoS composite material according to claim 1, characterized in that: In the solution A, the mass volume ratio of Co(NO3)2·6H2O to methanol is 1.2-2g:50-100ml.

3. The method for preparing the Co@CoS composite material according to claim 1, characterized in that: In the solution B, the molar concentration of dimethylimidazole is 300-500×10 -3 The mass volume ratio of mol / L dimethylimidazole and methanol is 3-4.2g:50-100ml.

4. The method for preparing the Co@CoS composite material according to claim 1, characterized in that: The stirring, wherein the stirring speed is 300-400 r / min, and the stirring time is 0.5-1 min.

5. The method for preparing the Co@CoS composite material according to claim 1, characterized in that: The self-reaction time is 12 to 15 hours.

6. The method for preparing the Co@CoS composite material according to claim 1, characterized in that: The mass ratio of the Co-ZIF to the sulfur powder is 1:2-4.

7. The method for preparing the Co@CoS composite material according to claim 1, characterized in that: The calcination process comprises a calcination temperature of 650 to 800° C., a calcination time of 1 to 3 hours, and a heating rate of 30 to 50° C. / min.

8. A Co@CoS composite material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the Co@CoS composite material as claimed in claim 8 in the preparation of a nano gas sensor, characterized in that: include, The Co@CoS composite material of claim 8 is dissolved in ethylene glycol, and after being evenly dispersed, it is coated on the built-in platinum interdigital electrodes of the sensor using a silk screen plate; vacuum drying is performed to form a stable film of the Co@CoS composite material to cover the interdigital electrode sensing area, thereby obtaining a Co@CoS composite material nano gas sensor; Wherein, the vacuum drying time is 8 to 12 hours.

10. The nano gas sensor based on Co@CoS composite material according to claim 9, characterized in that: The nano gas sensor is used for detecting the decomposition components of SF6 / N2 in a gas-insulated combined electrical appliance.